GRAFT CHOICE FOR ACL RECONSTRUCTION IN YOUNG ACTIVE PATIENTS – USE OF QUADRICEPS TENDON AUTOGRAFT INCREASED LIKELIHOOD OF MEETING RETURN TO PLAY CRITERIA AT 6 MONTHS POST SURGERY. Issue 4 (28th April 2020) - Gregory, Bonnie; Magill, John; Meyers, Heather; Pietrosimone, Laura; Le, Daniel; Reinke, Emily; Riboh, Jonathan
Background: ACL graft tears and contralateral injuries are problematic in pediatric sports medicine, with a combined incidence of 25-35%. Recent publications have highlighted a high failure rate with hamstring autografts in young patients, while others have suggested lower failure rates with quadriceps autografts. However, little is known about the possible reasons for this difference. Hypothesis: We hypothesized that the use of quadriceps soft tissue autografts would lessen post-operative neuromuscular deficits compared to other autografts, and therefore, young athletes would achieve objective return to sport (RTS) criteria more rapidly. Methods: A retrospective review of consecutive patients who underwent ACL reconstruction by a single surgeon and completed a comprehensive series of physical performance tests (PPTs) at 6 months post-surgery was conducted. A chart review of demographic and surgical data was completed. Patients performed nine common PPTs; limb symmetry index (LSI) was established and LSI> 90% was used as the cut-off for passing each individual test. Athletes met RTS criteria if they achieved LSI>90% on at least 8 of 9 tests. Multivariate linear and logistic regressions were performed to assess the effect of age (dichotomous; pediatric (<16 years) versus skeletally mature), gender, graft type, concomitant meniscal surgery, and time post-op, on the number of tests an individual could pass and the likelihood of passing the battery of PPTs, respectively. Results: The cohort of 68 young, active patients (mean age= 18.9 years +/- 7.5; 56% pediatric; 46% female; graft type: 63% BTB, 16% hamstring, 15% quadriceps, 6% ITB) were tested at a mean 6.7 months +/- 1.9. Overall, 35% of patients "passed" the battery of PPTs. Upon logistic regression, age and concomitant meniscal surgery were poor predictors of "passing." In contrast, use of quadriceps was a strong predictor of passing (OR 14.1, 95% CI 2.4-83, p=0.003, compared to BTB). Upon linear regression, use of quadriceps was again a strong predictor of the number of individual PPTs passed (b=1.8, 95% CI 0.33-3.3, p=0.02, compared to BTB). No other demographic variables predicted "passing" or number of individual PPTs passed. Conclusion: Young, active patients undergoing ACL reconstruction with quadriceps autograft are 14 times more likely to meet RTS criteria at 6 months post-op than similar patients with BTB, hamstring or ITB autograft. This may provide valuable insight into the decreased failure rates suggested with the quadriceps autograft. Additionally, this study confirms the majority of these high-risk, young athletes do not meet RTS criteria at 6 months post-operatively.